Acute myeloid leukemia with cup-like blasts and FLT3-ITD and NPM1 mutations mimics features of acute promyelocytic leukemia: a case of durable remission after sorafenib and low-dose cytarabine. Issue 1 (January 2022) - Sun, Jie; Ning, Shangyong; Feng, Ru; Li, Jiangtao; Wang, Ting; Xing, Baoli; Zhu, Xiaoquan; Zhao, Yanyang; Pei, Lei; Liu, Hui
Abstract : Some previous researches raised the possibility of a novel acute myeloid leukemia (AML) entity presenting cup-like cytomorphology with mutations of both FLT3 and NPM1 or one of them. However, the clinical implications of this subtype remain unknown. We describe a 63-year-old patient belonging to this distinct AML subtype, who presented similar features of acute promyelocytic leukemia (APL) including nuclear morphology, negative for CD34 and HLA-DR, and abnormal coagulation. He had no response to both arsenic trioxide and CAG regimen (cytarabine, aclarubicin, and G-CSF). Given that the patient carried the FLT3-ITD mutation, we switched to a pilot treatment of FLT3 inhibitor sorafenib combined with low-dose cytarabine (LDAC). To date, the patient achieved durable complete remission over 58 months. These findings suggest that AML with cup-like blasts and FLT3-ITD and NPM1 mutations mimic APL, and the prognosis of this subtype may be improved by sorafenib combined with LDAC.